Prognostic Value of Serum Uric Acid Level in Patients with ST Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Momen, Abdul; Uddin, Mir Jamal; Alam, Md Nur; Khair, Abul; Gosh, Sujit Kumar; Huq, Md Tanvirul; Bhuiyan, Md Hasan Faruque; Rahaman, Md Shajadur (University Heart Journal, 2025)
Background: All major kinds of cardiovascular disease-related mortality, such as acute, subacute, and chronic coronary artery disease, heart failure, and stroke, have been linked to serum uric acid levels. This study was conducted to evaluate prognostic value of serum uric acid in patients with ST elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI). Methods: This prospective observational study was conducted at Department of Cardiology at National Institute of Cardiovascular Diseases (NICVD), Dhaka, for a period of 24-months following ethical approval. A total 100 STEMI patients who underwent primary PCI were included after getting written informed consent. Based on the basal serum uric acid level, patients were categorized into tertiles. Patients with low serum uric acid (n = 50) were defined as having a value in the lower two tertiles (6.4 mg/dl). Data were collected in separated case record form and analyzed by SPSS 26.0. Results: Comparing with high serum uric acid group, the low serum uric acid group had better survival and a lower incidence of other major adverse cardiac events (MACE) (P = 0.027) and advanced heart failure as well as better KILLIP class (P = 0.028), better TIMI flow (P = 0.002), and a higher ejection fraction (49.2 ± 2.7 versus 42.3 ± 2.1; P = 0.001) during in hospital and three month follow up. Logistic regression shows that, TIMI Flow (OR=7.045, 95% CI=5.383-49.569, p=0.002), LVEF (%) (OR=2.419, 95% CI=1.054-5.554, p=0.037) and serum uric acid level (OR=19.879, 95% CI=0.786-23.069, p=0.030) were significantly associated risk factors for MACE. Conclusion: High serum uric acid level is associated with increased in-hospital and short-term major adverse cardiovascular events (MACE) in patients with acute STEMI undergoing primary PCI. University Heart Journal 2024; 20(2): 49-55